2023
DOI: 10.1001/jamanetworkopen.2023.10650
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Waning of SARS-CoV-2 Vaccine–Induced Immunity

Abstract: ImportanceEstimates of the rate of waning of vaccine effectiveness (VE) against COVID-19 are key to assess population levels of protection and future needs for booster doses to face the resurgence of epidemic waves.ObjectiveTo quantify the progressive waning of VE associated with the Delta and Omicron variants of SARS-CoV-2 by number of received doses.Data SourcesPubMed and Web of Science were searched from the databases’ inception to October 19, 2022, as well as reference lists of eligible articles. Preprints… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
71
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(73 citation statements)
references
References 67 publications
0
71
0
2
Order By: Relevance
“…Waning of vaccine protection during the ancestral and Alpha phases is not considered; indeed, ancestral lineages were replaced by the Alpha variant a few weeks after the start of the vaccination campaign in Italy, and the waning of vaccine protection estimated in the literature during dominance of the Alpha variant is negligible 26,33 . Accordingly, we consider variant‐specific average durations of protection after two doses of vaccine and after a booster dose 34 . Shorter and longer durations of vaccine protection are explored in the sensitivity analyses (Table S4).…”
Section: Methodsmentioning
confidence: 99%
“…Waning of vaccine protection during the ancestral and Alpha phases is not considered; indeed, ancestral lineages were replaced by the Alpha variant a few weeks after the start of the vaccination campaign in Italy, and the waning of vaccine protection estimated in the literature during dominance of the Alpha variant is negligible 26,33 . Accordingly, we consider variant‐specific average durations of protection after two doses of vaccine and after a booster dose 34 . Shorter and longer durations of vaccine protection are explored in the sensitivity analyses (Table S4).…”
Section: Methodsmentioning
confidence: 99%
“…[6][7][8] To date, the neutralizing response remains the most widely used correlate of protection from COVID-19, 9 and some reports showed that the levels of neutralizing antibodies (nAbs) as well as vaccine efficacy tend to wane over time from infection or vaccination. [10][11][12] Nevertheless, the proportion of vaccinated individuals and people who experienced natural infection(s) is constantly increasing with a demonstrated benefit of hybrid immunity (infection plus vaccination-driven immunity) in neutralizing SARS-CoV-2. 12,13 It is a matter of debate to whom the updated XBB vaccine shot should be administered, 4,14 nevertheless, the target population for vaccination certainly includes elderly people and severely immunocompromised individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Although mRNA vaccines (Moderna mRNA-1273; Pfizer-BioNTech BNT162b2) induce durable germinal center B cells (GCB) responses for at least 6 months 69 , the serum neutralizing antibody responses wane within 3 to 6 months and decline further by 8 months, with an estimated half-life of approximately 60 days 1012 . Waning humoral antibody and emergence of resistant, highly transmissible variants correlate with an increased frequency of breakthrough infections in vaccinated individuals 13,14 .…”
Section: Introductionmentioning
confidence: 99%